Methodology to assess the environmental sustainability of timber structures. (1st July 2015) - Cuadrado, Jesús; Zubizarreta, Mikel; Pelaz, Belinda; Marcos, Ignacio
Graphical abstract: Highlights: This study presents an "Environmental Sustainability Index for Timber Structures". An environmental sustainability classification of timber structures is achieved. Its reliability has been tested through its application to a case study. It is easy to apply and it is flexible enough for use in different parts of the world. Abstract: Timber is a renewable material with excellent strength-to-weight ratios, insulating properties and it plays an important environmental role, acting as a CO2 sink. Public awareness of sustainability and its importance in the construction sector is growing day by day, encouraging the use of more sustainable materials, as is the case of timber. To assist in this goal, this study presents a methodology to prepare an "Environmental Sustainability Index for Timber Structures" (ESI-TS). In no way intended for comparison with other construction materials, the index arrives at an environmental sustainability classification, with its set of indicators and relevant weights.